Pengaruh Edukasi Emo-Demo Terhadap Kepatuhan Minum Obat Pasien Hipertensi Pada Peserta Prolanis - Ita Rifa’atul Mahmuda; Roisah Roisah; Ainul Yaqin Salam (Jurnal Rumpun Ilmu Kesehatan, 2023)
The problem of medication adherence in individuals with hypertension remains a challenge, even in developing countries. The purpose of this study was to determine the effect of Emo demo education on adherence to taking medication in hypertensive patients enrolled in the Prolanis program at Puskesmas Sumbersari Lumajang. This study was conducted at Sumbersari Health Center in March 2023. This study used a quasi-experimental research design with a one group pre-post test design. The purposive sampling technique was chosen to select a sample of 50 respondents. This study used the MMAS-8-4 (Morisky Medication Adherence Scale) questionnaire as a measuring tool for medication adherence. Statistical tests using the Wilcoxon Signed Rank test. Before the emo-demo, most of the 22 (44%) respondents were at a low level of compliance. After emo-demo education, most of the respondents were in moderate compliance 33 (66%) and high compliance 14 (28%).  The results of bivariate analysis show that Emo demo education has a significant effect on drug compliance in hypertensive patients participating in Prolanis, with a p-value of 0.000 which is smaller than the predetermined level of significance of 0.05. The provision of Emo Demo in health education with a focus on the target group is expected to be facilitated by the puskesmas. Effective medication adherence among hypertensive patients can improve control of blood pressure and prevent complications of the disease.